Demographic, genetic and phenotypic characteristics of centenarians in Italy: Focus on gender differences. (July 2017) - Montesanto, Alberto; De Rango, Francesco; Pirazzini, Chiara; Guidarelli, Giulia; Domma, Filippo; Franceschi, Claudio; Passarino, Giuseppe
Highlights: Centenarians do represent a model of successful ageing. Multidimensional analysis of centenarians has revealed many aspects of ageing. Longevity has shown gender-specific features at clinical and genetic level. In Italy, a significant N-S gradient in the F/M ratio among 100+ has been observed. Abstract: An impressive and coherent series of epidemiological data from different populations (New England Americans, Mormons, Ashkenazi Jewish, Icelandic, Okinawan Japanese, Italians) suggests that long-lived subjects able to reach the extreme limits of human life, such as centenarians and supercentenarians, represent an extraordinary and informative model to identify the mechanisms responsible for healthy aging and human longevity. In most studies, genetic, demographic and phenotypic characteristics of longevity are discussed separately. However, longevity is a very complex trait due to the complicated interactions of numerous genetic and environmental factors. It is therefore necessary to analyse centenarians with a multidimensional approach, trying to consider different aspects simultaneously. In this review we will focus on Italian centenarians, who have been extensively studied for many years with different approaches, in order to show their peculiarities and the emerging data from the studies carried out on this exceptional population.